Association of blood lactate accumulation with fat metabolism during exercise: method matters - Chavez-Guevara, Isaac Armando; Ferri-Marini, Carlo; Peric, Ratko; Egan, Brendan; Rubio-Valles, Mariazel; Duron-Borjas, Maria Cristina; Ramos, Arnulfo (International Journal of Sports Medicine, 2025)
This study examined if analytical procedures influence the relationship between lactate metabolism and fat oxidation during exercise in 54 young men (age: 27±7 y; body fat: 23±10%; VO2max: 46.9±10.2 mL·kg−1·min−1). The first lactate threshold was assessed using the log–log transformation of blood lactate and running speed (LT1log–log), an increase of 1 mM above the baseline (LT1Bsln1.0), and a fixed blood lactate concentration of 2 mM (LT1OBLA2). The second lactate threshold was determined using the maximal distance approach (LT2Dmax) and a fixed lactate concentration of 4 mM (LT2OBLA4). The highest (FATmax) and lowest (FATmin) fat oxidation rates were determined using a third-degree polynomial regression (P3), visual inspection, and mathematical modeling (SIN). FATmax and FATmin showed the strongest correlation with LT1log–log (r: 0.65, p<0.01) and LT2OBLA4 (r: 0.81, p<0.01), regardless of fitness. FATmaxP3 and LTOBLA2 showed the best agreement in untrained individuals. Conversely, FATmaxP3 and LT1log–log showed the best agreement in obese men and trained subjects. LT2OBLA4 showed the best agreement with FATmin. When investigating the association between fat oxidation and lactate metabolism during exercise, LT1log–log and LT2OBLA4 should be computed, while mathematical modeling or visual analysis should be applied for FATmax, depending on the fitness level.
Keywords: exercise physiology; metabolism; physical fitness; training and testing